2005
DOI: 10.1021/om040127n
|View full text |Cite
|
Sign up to set email alerts
|

The SiOH-Containing α-Amino Acid HOMe2SiCH2CH(NH2)COOH and Its Immobilization on Silica via an Si−O−Si Linkage

Abstract: The R-amino acid ester rac-PhMe 2 SiCH 2 CH-(NH 2 )COOEt (rac-4) was transformed into the disiloxane RMe 2 SiOSiMe 2 R (5; R ) CH 2 CH(NH 2 )COOH) via an Si-C(Ph) cleavage in boiling hydrochloric acid. Upon dissolution of 5 in water, spontaneous formation of the racemic SiOH-containing R-amino acid HOMe 2 SiCH 2 -CH(NH 2 )COOH (rac-6) occurred, which could be immobilized on silica via an Si-O-Si linkage between the R-amino acid and the silica support (characterization by solid-state NMR spectroscopy). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…The following hydrolysis, to afford silanediol 19, was carried out using NaOD in [D 3 ]MeCN/D 2 O, to enable monitoring of the reaction and characterization of the product by 1 H NMR. Unencumbered silanediols are at risk of polymerization; [39,42] to decrease the risk of polymerization the reaction mixture was used directly in the enzymatic assay (Scheme 3).…”
Section: Chemistrymentioning
confidence: 99%
“…The following hydrolysis, to afford silanediol 19, was carried out using NaOD in [D 3 ]MeCN/D 2 O, to enable monitoring of the reaction and characterization of the product by 1 H NMR. Unencumbered silanediols are at risk of polymerization; [39,42] to decrease the risk of polymerization the reaction mixture was used directly in the enzymatic assay (Scheme 3).…”
Section: Chemistrymentioning
confidence: 99%
“…We sought bioorthogonal, single-bond linkers with the flexibility to conform to the demands of linking pharmacophoric sites while maintaining good drug-like properties and evading metabolism and conjugation. In earlier studies, Tacke et al installed silanol moieties in place of carbinols of known drugs, and demonstrated the retention of biological activity in vitro and in vivo, good stability, toleration, and pharmacokinetics, with resistance to dehydration and metabolism, and no detectable glucuronide conjugates [57]. In several instances, disiloxane dimers of these silanol drug analogs were noted in the solid state and concentrated solutions, but dimers were not exploited and did not appear to contribute to the pharmacology [58].…”
Section: Discussionmentioning
confidence: 99%
“…Under these strongly acidic CO conditions the phenylsilane was also hydrolyzed. This phenylalanine derivative was found to be monomeric when dissolved in water, but exclusively dimeric 43 when isolated [25]. An unexpected preparation of silanol 42 occurred when diazido amino acid 44 was reduced catalytically [26].…”
Section: Synthesis Of B-silylalanine and Derivativesmentioning
confidence: 98%